2014
DOI: 10.1080/09593330.2014.909888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pine bark on the biotransformation of trinitrotoluene and on the bacterial community structure in a batch experiment

Abstract: Pine bark, a low-cost industrial residue, has been suggested as a promising substitute for granular activated carbon in the on-site treatment of water contaminated with 2,4,6-trinitrotoluene (TNT). However, the complex organic structure and indigenous microbial community of pine bark have thus far not been thoroughly described in the context of TNT-contaminated water treatment. This two-week batch study examined the removal efficiency ofTNT from water by (1) adsorption on pine bark and (2) simultaneous adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…1). The biotransformation pathway is described in greater detail elsewhere (Chusova et al 2014). The respective mass balance calculations are presented in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The biotransformation pathway is described in greater detail elsewhere (Chusova et al 2014). The respective mass balance calculations are presented in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a previous study by Chusova et al (2014) indicated that in addition to its adsorptive capacity, pine bark also harbors bacterial groups capable of survival and growth in the presence of TNT water solution. TNTladen pine bark, contrary to activated carbon, can either be composted on-site or co-digested with other, more easily degradable substrates for methane production.…”
Section: Introductionmentioning
confidence: 96%
“…The first culture, subsequently referred to as In1, co-metabolised TNT (0.4 mM), while the second culture, referred to as In2, co-metabolised the previously described TNT-contaminated industrial sludge mixed with water (1.5 -2.0% v/v). The cultures were transferred weekly into fresh mineral salt medium M9* [8] containing glucose and TNT in the case of In1 and glucose and sludge particles in the case of In2.…”
Section: Isolation and Culture Conditions Of Inoculamentioning
confidence: 99%
“…This adsorbent has also been studied for the removal of organic pollutants such as PAHs [4], bisphenol [5], estradiol (E2) [6] and lindane [7] from contaminated water. Chusova et al [8] showed that pine bark can effectively remove TNT from pink water, a wastewater generated during the process of demilitarization of explosives at army ammunition plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation